PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP HARGA SAHAM - Helmiati Helmiati (Ensiklopedia of Journal, 2026)
This research aims to determine the effect of Profitability and Leverage simultaneously and partially on Share Prices in Mining Companies in the Coal Sub Sector Listed on the Indonesia Stock Exchange in 2020-2022. The sample determined in this research was 11 companies with the criteria desired by the author and hypothesis testing used multiple linear regression analysis with the help of SPSS V 25 for Windows. The data collection technique used in this research is the documentation method. Based on the results of simultaneous tests, the Profitability and Leverage variables influence share prices in mining companies in the coal sub-sector listed on the Indonesian Stock Exchange in 2020-2022. Meanwhile, partially the two variables Profitability and Leverage have an influence. The close relationship that occurs between the Profitability and Leverage variables on Share Prices is strong with the correlation coefficient (R) obtained at 52.8%.Keywords: Profitability, Leverage, Share PriceThis research aims to determine the effect of Profitability and Leverage simultaneously and partially on Share Prices in Mining Companies in the Coal Sub Sector Listed on the Indonesia Stock Exchange in 2020-2022. The sample determined in this research was 11 companies with the criteria desired by the author and hypothesis testing used multiple linear regression analysis with the help of SPSS V 25 for Windows. The data collection technique used in this research is the documentation method. Based on the results of simultaneous tests, the Profitability and Leverage variables influence share prices in mining companies in the coal sub-sector listed on the Indonesian Stock Exchange in 2020-2022. Meanwhile, partially the two variables Profitability and Leverage have an influence. The close relationship that occurs between the Profitability and Leverage variables on Share Prices is strong with the correlation coefficient (R) obtained at 52.8%. Profitability, Leverage, Share Price